Developing EFL writing with year 5 pupils by writing summaries - Puhner, Nataša (ELOPE (Ljubljana), 2018)
Developing EFL writing skills in primary school pupils is one of the most demanding and time consuming challenges that foreign language teachers face. The main aim of this study was thus to analyse 64 written summaries of Year 5 pupils in terms of content, structure, length and most often used words. In order to achieve the aim of pupils being able to write a summary of a story individually and in a given time frame, the task was approached gradually and systematically throughout the school year. The results show that most of the pupils managed to finish a structurally organized summary and most of them wrote a summary which included the most important aspects regarding the content of the story. The results of the survey indicate that a systematic approach to writing summaries helps pupils in developing their writing skills.
Keywords: angleščina kot tuji jezik; obnova; osnovnošolski učenci; pisna spretnost